Natural gas hydrate exploitation by CO2/H2 continuous Injection-Production mode. (15th September 2018) - Sun, Yi-Fei; Zhong, Jin-Rong; Li, Rui; Zhu, Tao; Cao, Xin-Yi; Chen, Guang-Jin; Wang, Xiao-Hui; Yang, Lan-Ying; Sun, Chang-Yu
Highlights: A novel natural gas hydrate exploitation by CO2 /H2 continuous injection-production mode was proposed. A balance between methane production and CO2 sequestration exists when the CO2 mole fraction was below 74%. Suitable composition range of injection gas and an efficient injection rate controlling strategy were suggested. A more economically feasible and more productive measure for NGH exploitation was proposed by regulating injection rate. Abstract: CO2 replacement is considered as a promising method for the simultaneous development of natural gas hydrate and CO2 sequestration. The addition of small molecular gases, such as N2 and H2, into the injected gas can increase the gas recovery ratio and prevent CO2 liquefaction. Based on previous studies, this work presents methane hydrate exploitation using the CO2 /H2 continuous injection-production mode. The mechanism combines gas sweep with CH4 /CO2 replacement. A series of experiments were carried out to optimize the injected gas composition and flow rate, which have a significant effect on the rate of CH4 hydrate decomposition, amount of CO2 sequestration, and cost. The compositions of the injected gases had little effect on the recovery rate when a relatively higher flow rate was employed. A balance between CH4 production and CO2 sequestration was established when the CO2 mole fraction was slightly <74%, and the temperature of the reservoir did not decline throughout the whole process. The injection rate affected both the displacement efficiency and the production cost. Moreover, through these experiments, we discovered a more economically feasible and productive measure for regulating the injection rate.